e-Commerce – Leaders and Customers - M. Aseri, Dr. Abdulah (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
e-Commerce like the technology it is representative changes every day across the global marketplace. In fact, to keep abreast of hot topics and trends from a business perspective, savvy e-Commerce businesses specifically keep watch for what is prodding those surfing and searching the Internet to jump at sales within their own industries. The following provides both a birds-eye view and an insider lens to who are the leaders and customers of e-Commerce today, and why. The following also specifically discusses the tremendous impact Amazon continues to have setting standards for best practices in e-Commerce. Other topics covered give insights on the demographics of who uses e-Commerce the most, and how Mobile-Commerce cannot be ignored to assure getting or maintaining a fair market share.